Primary epidural hemangiopericytoma of the thoracic spine: Case report and literature review. (February 2019) - Li, Ziquan; Deng, Yuzhoujia; Li, Zhimin; Wang, Tianyu; Gao, Jun; Zhou, Weixun; Li, Yongning; Wang, Yipeng
Highlights: We reported an epidural thoracic HPC case and presented largest review of 105 cases. Immunohistologic examination is of decisive importance in making the diagnosis. Total resection can be attempted for tumor with clear margin to relieve symptoms. PET may be considered in follow-up for early detection of recurrence and metastasis. Radio/chemotherapy are not preferred except for incomplete resection or recurrence. Abstract: Hemangiopericytoma (HPC) is a rare tumor originating from pericapillary cells. Rarely found in the central nervous system, it is extremely rare in the spinal canal. Because of the low incidence of this tumor, its radiographic features and clinical manifestations have not been extensively studied and reported, therefore, it is often misdiagnosed as a schwannoma or spinal meningioma. We describe an unexpected HPC in a 35-year-old woman who was admitted to the Peking Union Medical College Hospital with a severe backache, sensory abnormalities, and muscle weakness. Magnetic resonance imaging showed an enhancing lesion at T6–7 with severe compression of the spinal cord. Gross total resection was achieved, and subsequently, a marked neurologic improvement was observed. The diagnosis of primary extradural HPC in our patient was confirmed based on postoperative histopathology and immunohistochemistry. Neither recurrence nor metastasis of the tumor was found during the 14-month follow-up, which did not include radiotherapy. To describe the demography, radiologic features, treatment, and prognosis of spinal HPC, a comprehensive literature review was performed and 105 cases of primary spinal HPC from 1958 to 2017 were collected from 39 articles. Although rare, HPC should be considered in the differential diagnosis of intraspinal lesions. Immunohistologic examination is of decisive importance in making the diagnosis. Adequate surgical resection, when feasible, is the first choice of treatment for all cases of HPC; however, the outcomes of radiotherapy and chemotherapy have yet to be determined. Individualized treatment combined with long-term follow-up for each patient is recommended.